2015
DOI: 10.1093/schbul/sbu197
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Sequencing Indicates That the Oropharyngeal Phageome of Individuals With Schizophrenia Differs From That of Controls

Abstract: Mucosal sites such as the oropharynx contain a wide range of microorganisms, collectively designated as the microbiome. The microbiome can affect behavior through a number of neurobiological and immunological mechanisms. Most previous studies have focused on the bacterial components of the microbiome. However, the microbiome also includes viruses such as bacteriophages, which are viruses that infect bacteria and alter their metabolism and replication. We employed metagenomic analysis to characterize bacterioph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(89 citation statements)
references
References 33 publications
6
82
1
Order By: Relevance
“…Lactobacillus group bacterial numbers correlated positively with severity of psychotic symptoms and negatively with global assessment of functioning. The increased levels of lactobacilli in FEP patients are consistent with reports in autistic children (Adams et al, 2011) and with reports showing increased abundance of bacteriophage genome of Lactobacillus phage phiadh in human oropharyngeal samples of schizophrenia patients (Yolken et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Lactobacillus group bacterial numbers correlated positively with severity of psychotic symptoms and negatively with global assessment of functioning. The increased levels of lactobacilli in FEP patients are consistent with reports in autistic children (Adams et al, 2011) and with reports showing increased abundance of bacteriophage genome of Lactobacillus phage phiadh in human oropharyngeal samples of schizophrenia patients (Yolken et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…Higher incidence of lactic-acid bacteria in the oropharyngeal microbiome was reported, compared to controls (Castro-Nallar et al, 2015). Interestingly, a Lactobacillus specific phage was also discovered in high abundance (Yolken et al, 2015). Another study reported a blood-specific microbiome in schizophrenia patients, compared to controls, with higher alpha and beta diversity (Mangul et al, 2016; Severance et al, 2013).…”
Section: The Microbiome In Neurodevelopmental and Mood Disordersmentioning
confidence: 99%
“…Bacteriophages infect bacteria and subsequently alter their metabolism and replication, which could affect the composition of the microbiota and their ability to signal to the brain. The levels of the bacteriophage Lactobacillus phage phiadh were found to be elevated in the oropharyngeal microbiota in schizophrenic patients with comorbid immunological conditions [160]. The main Lactobacillus host for this bacteriophage is Lactobacillus gasseri , a strain of bacteria that is found in the oral and gastrointestinal mucosae and is linked with host immune modulation [161].…”
Section: The Gut–microbiota–brain Axis In Psychiatric and Neurodevelomentioning
confidence: 99%